Editorial Preface - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018), 2021)
Overview of the Idealogy of Arts and Social Science by the Chief and Deputy Chief Editor.